Henry More and Descartes on the passions of the soul. Issue 1 (2nd January 2022) - Bryson, James
ABSTRACT: Henry More's well-catalogued attack of Cartesian metaphysics has distracted scholars from exploring the reasons for the Cambridge Platonist's abiding attraction to Descartes's moral psychology. Even after he had become disillusioned with the implications of Descartes's substance dualism, More defended a moral vision that relied heavily on the Frenchman's treatise on the passions. Through a careful treatment of More's ethical philosophy as expressed in his Enchiridion Ethicum (1668) and of the implicit moral argument of Descartes's Passiones Animae (1650), this article explores the vast expanse of common ground these philosophers held in common. Fundamental to their shared moral vision is their conviction that the passions were fundamentally good and that they could be shaped by the will to defend against the effects of unbridled passion, including violence and atheism. More saw Descartes as an ally who also understood that the passions were the means by which the soul could become God-like.